Incidence of years of schooling and amount of reading in the lexical availability of one group of the university students of the area of pedagogy - Martínez-Lara, José Alejandro (Boletín de Filología, 2021)
In this research, we analyze the lexical availability (LD) of a group of Chilean university students according to variables related to their level of schooling and reading practices. We start from the hypothesis that, on the one hand, fourth-year students will have higher indexes of lexical availability (LDI) than first-year students. On the other hand, students who dedicate more hours per week to reading will have higher LDIs than those who dedicate little or no time to such cultural consumption. Thus, the objectives of this article are: 1) to describe the lexical flow of a group of students of the pedagogy career of the mentions of: Spanish and Philosophy, Biological Sciences and Kindergarten, of an institution attached to the Consejo de Rectores de Universidades Chilenas, with respect to three centers of interest (CI): Reading, Education and School: furniture and materials and 2) to describe the incidence of years of schooling and number of hours of reading in the lexicon. For this purpose, we have analyzed a sample, collected and edited according to the general criteria of the Proyecto Panhispánico de Léxico Disponible, and processed using the Dispogen program. The results have shown that the IC with the highest number of words was The school, while the IC with the highest number of words was Education. Concerning the years of schooling, there was an increase in the lexical stock of the students in their last year compared to those in their first year. Regarding the amount of reading, it could be seen that the more hours of reading, the higher the average number of words.